Doxorubicin-loaded N-naphthyl-N,O-succinyl chitosan micelles for colon cancer treatment - Kansom, Teeratas; Sajomsang, Warayuth; Chairoungdua, Arthit; Kitcharoen, Nudchanart; Charoensuksai, Purin; Patrojanasophon, Prasopchai; Opanasopit, Praneet (Science, Engineering and Health Studies, 2021)
Doxorubicin (Dox) is one of the effective treatments in many types of cancer, such as breast cancer and ovarian cancer. However, the clinical settings of this drug are limited by its low therapeutic efficiency and high toxicity to normal cells. To achieve better anticancer efficacy, Dox-loaded micelles were developed using the amphiphilic chitosan derivative N-naphthyl-N,O-succinyl chitosan (NSCS) through the dropping technique. The physicochemical properties including particle size, zeta potential, morphology, encapsulation efficiency (%EE), and loading capacity (LC) were evaluated. Results revealed that the Dox-loaded micelles were spherical in shape with a nanosized diameter (<200 nm) and negative charge (-30 mV). Incorporation of Dox into the micelles at the initial drug concentration of 40% w/w to the polymer provided the highest values of %EE (76.42%) and LC (305.68 μg/mg), reflecting that a high amount of drug could be encapsulated into the inner core of the micelles. Moreover, the Dox-loaded micelles exhibited higher cellular uptake compared with the free drug. In vitro cytotoxicity against HT29 colorectal cancer cells revealed that the Dox-loaded micelles had a greater inhibitory effect than the free drug with lower IC50 values. Therefore, these NSCS micelles may be potential nanocarriers to deliver Dox for colon cancer treatment.